Resisting agroextractivisms: analysis of actors and trajectories in defense of GMO-free Mayan and Embera territories (2002-2020) - López Arboleda, Beatriz; Barrera-Bassols, Narciso; Vélez-Torres, Irene (Agrociencia Uruguay, 2022)
This article is part of the result of PhD research on social mobilization against transgenics in Mexico and Colombia. In this case, we focus on agro-extractivism and its territorial control through the use of transgenic seeds. The dispute in this sense is given between small peasant producers stripped of their agroecological heritage and business producers attached to the hegemonic model of the agri-food sector. In the case of the Mayan people in Mexico and the Emberá in Colombia, articulated with various actors, they mobilize to defend their territories against transgenics. In this context, it is proposed as an objective to analyze the mechanisms used by the Mayans and Emberá to resist transgenics. The methodology focuses on an ethnographic perspective, on semi-structured interviews and on the review of secondary information. The results correspond to the mechanisms of resistance through declarations of GMO-Free Territories and claims for protection against the sowing of GMOs. The dialogue in these two experiences has resulted in achievements for the resistance on transgenics, although with the difficulties of a struggle that does not end in a free market context.